2022
DOI: 10.3390/v14030467
|View full text |Cite
|
Sign up to set email alerts
|

DEAD-Box RNA Helicase 21 (DDX21) Positively Regulates the Replication of Porcine Reproductive and Respiratory Syndrome Virus via Multiple Mechanisms

Abstract: The porcine reproductive and respiratory syndrome virus (PRRSV) remains a persistent hazard in the global pig industry. DEAD (Glu-Asp-Ala-Glu) box helicase 21 (DDX21) is a member of the DDX family. In addition to its function of regulating cellular RNA metabolism, DDX21 also regulates innate immunity and is involved in the replication cycle of some viruses. However, the relationship between DDX21 and PRRSV has not yet been explored. Here, we found that a DDX21 overexpression promoted PRRSV replication, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…The subcellular distribution of DDX21 into nucleolus is required for the RNA unwinding ( Song et al, 2017 ). DDX21 regulates viral replication through many ways, including inhibiting viral genome replication and prohibiting virus replication ( Watanabe et al, 2009 ; Abdullah et al, 2021 ; Li et al, 2022b ; Zhao et al, 2022 ). DDX21 interacts with rRNAs and snoRNAs to facilitate transcription and processing ( Flores-Rozas and Hurwitz, 1993 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subcellular distribution of DDX21 into nucleolus is required for the RNA unwinding ( Song et al, 2017 ). DDX21 regulates viral replication through many ways, including inhibiting viral genome replication and prohibiting virus replication ( Watanabe et al, 2009 ; Abdullah et al, 2021 ; Li et al, 2022b ; Zhao et al, 2022 ). DDX21 interacts with rRNAs and snoRNAs to facilitate transcription and processing ( Flores-Rozas and Hurwitz, 1993 ).…”
Section: Discussionmentioning
confidence: 99%
“…The primers used are listed in Table 1. Cell transfection was conducted as previously described (Zhou et al, 2022b).…”
Section: Plasmid Construction and Cell Transfectionmentioning
confidence: 99%
“…During PRRSV infection, DDX18 redistributes from nucleus to cytoplasm and interacts with NSP2 and NSP10, to promote virus replication ( Jin et al, 2017 ). DDX21 is also translocated from nucleus to cytoplasm and then positively regulates the PRRSV replication by stabilizing the expression of PRRSV NSP1α, NSP1β, and N protein ( Li et al, 2022 ). It has been found that DDX21 interacts with NSP1β, which enhances the expression of DDX21.…”
Section: Regulation Of Rna Synthesismentioning
confidence: 99%